Reducing Corruption in Public Education Programs in Africa:Instruments and Capture in Madagascar - Nathalie Francken (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2009)
This paper investigates how the choice of public expenditure instrument is affecting capture in the public education sector. We analyze data on two public funding schemes in Madagascar. We find that there is much more capture of in-kind transfers than of cash transfers. Capture of both instruments declines with better local access to media infirmation and with higher local literacy rates. However, capture of cash grants falls rapidly with a raise in the level of education of the intended beneficiaries, while this effect is significantly weaker for capture of in-kind funds. Our findings suggest that intensive monitoring and increased public access to infirmation should be combined with the right instrument for public funding implementation in order to eradicate capture and corruption.
Keywords: H52; I22; 330; Public Expenditures; Transparency; Media; Öffentliche Bildungsausgaben; Korruption; Sachtransfer; Informationsverbreitung; Humankapital; Madagaskar